From Cybernetics to Systems Theory in the First Space Age - Christian Girard (Footprint)
The first space age offers a remarkable context to scrutinise the inverse fates of cybernetics and systems theory in the 1960–70s, the latter taking the place of the former thanks to its operational effectiveness. Both fields appeared to tackle the pilot problem head-on, either to shoot a pilot down (cybernetics in World War II) – or to send some to the moon and back (systems engineering and management in the Apollo programme). The study of three US institutions (TRW, SDC and NASA) demonstrates an intense alliance between them, with a persistent focus on the issues of automation and systems thinking. A selection of written documents produced by each entity shows with utmost clarity their high degree of involvement in a post-cybernetics systemic approach. Incidentally, those analyses also show how the differences and similarities between old space and new space reveal themselves in light of the pilot problem. Overall, the pilot’s role reconfigured the man/machine assemblage as much as the pilot was reconfigured by that assemblage, with the critical assistance of computation.